Optimal management of sarcopenia - Louise A Burton (Dove Medical Press, 2010)
Louise A Burton, Deepa SumukadasAgeing and Health, Division of Medical Sciences, University of Dundee, Dundee, Scotland, United KingdomAbstract: Sarcopenia is the progressive generalized loss of skeletal muscle mass, strength, and function which occurs as a consequence of aging. With a growing older population, there has been great interest in developing approaches to counteract the effects of sarcopenia, and thereby reduce the age-related decline and disability. This paper reviews (1) the mechanisms of sarcopenia, (2) the diagnosis of sarcopenia, and (3) the potential interventions for sarcopenia. Multiple factors appear to be involved in the development of sarcopenia including the loss of muscle mass and muscle fibers, increased inflammation, altered hormonal levels, poor nutritional status, and altered renin–angiotensin system. The lack of diagnostic criteria to identify patients with sarcopenia hinders potential management options. To date, pharmacological interventions have shown limited efficacy in counteracting the effects of sarcopenia. Recent evidence has shown benefits with angiotensin-converting enzyme inhibitors; however, further randomized controlled trials are required. Resistance training remains the most effective intervention for sarcopenia; however, older people maybe unable or unwilling to embark on strenuous exercise training programs.Keywords: aged, muscle function, sarcopenia